Are metals of antifouling paints transferred to marine biota? (Brazilian Journal of Oceanography, 2007)
Because of its high toxicity, TBT (trybutiltin) was banned since 2003, which resulted in a greater re-use of Cu as based-biocide in antifouling paints (AFP). The aim of this work is to determine if metals form of AFP are transferred to benthic organisms from Guanabara Bay (GB) (Rio de Janeiro, Brazil). Metal concentrations were measured in two main fouling algae species Ulva flexuosa and U. fasciata and one isopod species, Sphaeroma serratum, in two GB marinas areas from sites with artificial substrate covered by AFP and natural substrate.In addition, control samples were collected in an adjacent open ocean area. Concentrations of Cd, Cr, Cu, Pb and Zn were determined by Atomic Absortion Spectrophotometry. Higher concentrations of Cu, Pb and Zn were detected in both algal species from GB in relation to control areas. Among samples of algae and isopod species from GB, populations collected over artificial surfaces covered by AFP presented significantly higher metal concentration than population of rocky natural substrate. Our data showed that the leaching of metals by antifouling paints present on decks and boats are being taken up by algae and isopods. These results indicate that antifouling coatings are the main source of heavy metal to biota of GB marina area.